GPS and integer estimation - Teunissen, Peter (Issued by Wiskundig Genootschap, Amsterdam., 2004)
The Global Positioning System (GPS) nowadays is used for a whole variety of positioning and navigation applications. These applications range from navigating your private sailboat to determiningthe millimeter movements of the earth’s tectonic plates. For the very high-accuracy applications of GPS one needs very precise range information. These precise ranges for positioning with GPS are obtained from carrier phase measurements. These measurements of range inherently contain unknown integer ambiguities to account for the mismatch of a whole number of wavelengths or cycles. This contribution describes the problem of GPS carrier phase ambiguity resolution, discusses some relevant elementsof integer estimation theory and reviews some of the high precision positioning applications that come into reach when the integer carrier phase ambiguities can be resolved quickly and correctly.